ORTHOGRAPHIC CROSSLINGUISTIC INFLUENCE ON THIRD LANGUAGE PRONUNCIATION: A CASE OF ADVANCED STUDENTS READING FOR A BA DEGREE IN ENGLISH - BEGHOUL, Youcef (Journal of Human Sciences, 2008)
This paper is a contribution to the recent rationalist, multidimensional, and multidirectional trend in explaining the notion of language transfer, now “crosslinguistic influence”, as a conscious problem solving process rather than as an unconscious and mechanistic operation. It also provides support to those who believe that the role of a second language is no less important in shaping the learner’s interlanguage. This is done through analysing some of the pronunciation errors of three groups of BA students of English: those that are the result of an orthographic crosslinguistic influence from French, their second standard language after Arabic.